Undifferentiated Embryonal Sarcoma of the Liver: An Enigma of Diagnosis - Ariffin, AC; Hayati, F; Azizan, N; Zuhdi, Z; Azman, A; Othman, HA; Jarmin, R (Gazi Univ, Fac Med, 2024)
A 20-year-old man presented with peritonitis requiring emergency laparotomy. He was found to have a huge liver abscess on the right lobe. Open drainage was performed but the abscess was persistently unresolved upon follow up. Computed tomography (CT) revealed a solid liver lesion with raised Ca 19-9. Right hepatectomy was subjected and histology was consistent with a rare and aggressive case of embryonal sarcoma of the liver. Despite oncologic resection, he developed local recurrence and succumbed to death in 6 month postoperatively. We describe a unique aetiology of liver abscess with literature reviews of undifferentiated embryonal sarcoma of the liver.